Competitive strategy - Grant, Robert (Henry Stewart Talks, 2013)
Competitive strategy, Business strategy, Competitive advantage, Industry attractiveness -Michael Porter, Five forces of competition, Competitive positioning, Key success factors
Reviewed at 2021/07/27